Methodological adaptations to a theory of change model: Experiences from the ARTEMIS cluster randomized trial in India - Sandhya Kanaka Yatirajula; Sudha Kallakuri; Srilatha Paslawar; Ankita Mukherjee; Naushad Alam Khan; Graham Thornicroft; Pallab K. Maulik (Elsevier, 2022)
This article discusses methodological adaptations that were made to the Theory of Change (ToC) process by incorporating imagery during a ToC workshop organized as part of a cluster randomize control trial in India, entitled ARTEMIS. The objective of this adaptation was to make the ToC interesting and interactive for adolescents who are the primary stakeholders in the project. This in turn led to a demystification of the concepts of ToC making it easier for participants of the workshop to contribute more effectively. An added advantage of such adaptations was that it allowed for engaging with specific groups using non-traditional strategies and adapting methods to local needs to make them more effective. Such an exercise will contribute to strengthening of the evidence base on the usefulness of adapting and simplifying methods as well as add to the body of participatory or collaborative visual research by promoting the use of visual material.